Motivations and Goals of Slow Tourism. (February 2016) - Oh, Haemoon; Assaf, A. George; Baloglu, Seyhmus
The concept of slow tourism is gaining attention, and this study provides new insights into the phenomenon from the perspective of a goal-driven consumption process. The authors conduct primary qualitative research to define slow tourism, build a conceptual model, and develop measurement scales. Based on the data collected from four popular U.S. tourist destinations, the authors find that goal-driven consumption theory exhibits compelling explanatory power for the slow behavioral process in the tourism context. The slow tourism process also appears to coexist with fast modes of travel and they contribute differently to general tourism experience outcomes. Discussion includes approaches to understanding the slow tourism phenomenon, issues around slowness in human behavior, and future directions for research on slow tourism.